Persisting in tough times across Hong Kong, mainland China, and the Philippines: grit, achievement goal orientation, and science engagement - Jesus Alfonso D. Datu; Ming Ming Chiu; Nino Jose Mateo; Lan Yang (SpringerOpen, 2024)
Abstract Background Past studies of grit's educational benefits, such as science engagement, showed mixed results across cultures. So, we elaborated the prior model of grit (perseverance of effort, consistency of interest) with adaptability to situations (forming a triarchic model of grit TMG), and tested TMG's relation to subsequent science engagement. Methods In this study, 1,972 high school students in Hong Kong, mainland China, and the Philippines completed surveys twice (about 6 months apart). We analysed these data with multilevel structural equation modelling. Results Results showed that country income (GDP per capita) negatively predicted science engagement, while schools with the highest ability students had higher science engagement. Conscientiousness and overall grit positively predicted science engagement at both time periods. Consistency of interest negatively predicted science engagement. Conclusions This research demonstrates the potential academic benefits of grit in non-Western societies. Promoting grit may serve as a pathway towards greater students' engagement in science.